Astragaloside IV Derivative (LS-102) Alleviated Myocardial Ischemia Reperfusion Injury by Inhibiting Drp1Ser616 Phosphorylation-Mediated Mitochondrial Fission - Chen, Li; Chen, Xiao-Yi; Wang, Qian-Long; Yang, Si-Jin; Zhou, Hua; Ding, Li-Sheng; Qing, Lin-Sen; Luo, Pei (Frontiers in Pharmacology, 2020)
Our previous study showed that Astragaloside IV derivative (LS-102) exhibited potent protective against ischemia- reperfusion (I/R) injury, but little has known about the mechanisms. Mitochondrial fission regulated by dynamin-related protein1 (Drp1) is a newly recognized determinant of mitochondrial function. The objective of this study was to investigate the protection of LS-102 on mitochondrial structure and function by regulating the activity of Drp1. These models of hypoxia- reperfusion (H/R) inducing injury of H9c2 cardiomyocytes and I/R inducing injury of rat heart were used. From our results, LS-102 significantly decreased apoptosis, the levels of ROS, CK, LDH and calcium, increased MMP and the Bax/Bcl-2 ratio in cardiomyocytes. Furthermore, LS-102 prevented I/R-induced mitochondrial fission by decreasing Drp1's mitochondrial localization through decreasing the phosphorylation of Drp1 at Ser616 (Drp1Ser616) and increasing the phosphorylation of Drp1 at Ser637 (Drp1Ser637) in H9c2 cells. Importantly, we also robustly confirmed Drp1Ser616 as a novel GSK-3β phosphorylation site. GSK-3β-mediated phosphorylation at Drp1Ser616 may be associated with mitochondrial fission during I/R of cardiomyocytes. In conclusion, LS-102 exerts cardioprotection against I/R-induced injury by inhibiting mitochondrial fission via blocking GSK-3β-mediated phosphorylation at Ser616 of Drp1.